Evidence for in vitro and in vivo expression of the conserved VAR3 (type 3) plasmodium falciparum erythrocyte membrane protein 1 - Wang Christian W (Malaria Journal, 2012)
Abstract Background Members of the Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) adhesion antigen family are major contributors to the pathogenesis of P. falciparum malaria infections. The PfEMP1-encoding var genes are among the most diverse sequences in nature, but three genes, var1, var2csa and var3 are found conserved in most parasite genomes. The most severe forms of malaria disease are caused by parasites expressing a subset of antigenically conserved PfEMP1 variants. Thus the ubiquitous and conserved VAR3 PfEMP1 is of particular interest to the research field. Evidence of VAR3 expression on the infected erythrocyte surface has never been presented, and var3 genes have been proposed to be transcribed and expressed differently from the rest of the var gene family members. Methods In this study, parasites expressing VAR3 PfEMP1 were generated using anti-VAR3 antibodies and the var transcript and PfEMP1 expression profiles of the generated parasites were investigated. The IgG reactivity by plasma from children living in malaria-endemic Tanzania was tested to parasites and recombinant VAR3 protein. Parasites from hospitalized children were isolated and the transcript level of var3 was investigated. Results Var3 is transcribed and its protein product expressed on the surface of infected erythrocytes. The VAR3-expressing parasites were better recognized by children´s IgG than a parasite line expressing a Group B var gene. Two in 130 children showed increased recognition of parasites expressing VAR3 and to the recombinant VAR3 protein after a malaria episode and the isolated parasites showed high levels of var3 transcripts. Conclusions Collectively, the presented data suggest that var3 is transcribed and its protein product expressed on the surface of infected erythrocytes in the same manner as seen for other var genes both in vitro and in vivo. Only very few children exhibit seroconversion to VAR3 following a malaria episode requiring hospitalization, supporting the previous conclusion drawn from var3 transcript analysis of parasites collected from children hospitalized with malaria, that VAR3 is not associated with severe anaemia or cerebral malaria syndromes in children.